THE EXODUS AND IDENTITY FORMATION IN VIEW OF THE YORUBA ORIGIN AND MIGRATION NARRATIVES - Olojede, Funlola (Scriptura, 2011)
Certain elements of the origin and migration narratives of the Yoruba such as a common ancestor, common ancestral home, common belief in the Supreme Deity provide a basis for identity formation and recognition among the people. It is argued that the narratives help to bring to light the memories of the Exodus and Israel's recollection of Yahweh as the root of its identity. The juxtaposition of cosmogonic myths and migration theories foregrounds the elements of identity formation of the Yoruba people and have a parallel in the blending of both cosmic and migration elements in Exodus 14-15:18. This blending also points out clearly the role of Yahweh as the main character in the Sea event. doi: 10.7833/108-1-7